Effect of high pressure processing or freezing technologies as pretreatment in vacuum fried carrot snacks. (February 2016) - Albertos, I.; Martin-Diana, A.B.; Sanz, M.A.; Barat, J.M.; Diez, A.M.; Jaime, I.; Rico, D.
Abstract: Vacuum fried carrot snacks were prepared using high pressure processing or freezing as pretreatment before the vacuum frying process. Physicochemical, organoleptic and antioxidant parameters were evaluated in order to determine the effect of pretreatment on the final product. The results showed that the use of high pressure and freezing pretreatments had significant effects on the final product. Both pretreatments caused cell modification, as observed from microstructural analysis. Pretreatment application helped in maintaining phenolic content and antioxidant capacity of the samples, effect which could be observed over storage. Freezing pretreatment increased crispness values of the samples, as compared to HPP-pretreated or control samples. On the other hand, freezing pretreatment also favoured oil absorption. The use of the proposed pretreatments (HPP or freezing) resulted in a feasible approach for improving the nutritional and organoleptic properties of vacuum-fried carrot snacks. Industrial relevance: Vegetable consumption remains lower than the recommended intake by health authorities. One possible strategy to increase the consumption of vegetable is the development of snacks. Most of vegetable snacks in the market are made through drying. However, dried products are far from the textural, appearance and mouthfeel properties of deep-fried products. The use of vacuum frying is an option for the development of appealing and yet healthy vegetable snacks. Nevertheless, pre-treatments are required to provide adequate final texture. To this regard, most studies are focused on osmotic pre-treatments. This study demonstrated that freezing and HPP pretreatments can be successfully applied in order to obtain crispy carrot chips. Furthermore, the use of pretreatments helped to maintain phenolic content and antioxidant capacity of the snacks. Highlights: Development of novel crispy carrot snacks using vacuum frying Use of physical pretreatments improved antioxidant properties of carrot snacks. Freezing pretreatment enhanced textural properties of fried carrot snacks.